2003
DOI: 10.1103/physrevb.67.195333
|View full text |Cite
|
Sign up to set email alerts
|

Exciton migration inβ-phase poly(9,9-dioctylfluorene)

Abstract: We have studied the dynamics of optically generated excitations in spin-coated glassy films of poly͑9,9-dioctylfluorene͒ ͑PFO͒ and in ␤-phase PFO films using picosecond time resolved photoluminescence ͑PL͒ spectroscopy, performed both at room temperature ͑RT͒ and at 5 K. We also present measurements of the PL emission of PFO and ␤-phase PFO at RT and 5 K following continuous wave ͑cw͒ excitation. We show that the cw emission from ␤-phase PFO at 5 K is very highly resolved, permitting us to make an assignment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
187
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(214 citation statements)
references
References 49 publications
18
187
1
8
Order By: Relevance
“…17 The emission vibronic peaks identified in Figure 1 at 2.82, 2.65, and 2.48 eV match the values of 2.81, 2.65, and 2.49 eV of the -phase emission spectrum in PFO films at room temperature. 13 The similarity between the fluorescence spectrum of PFO/ MCH solutions obtained upon excitation at 438 nm and that of the nearly planar ladder-type polymer MeLPPP, where fluorescence originates from an isolated chain, is in agreement with the PFO emission resulting from PFO chain segments with a more planar ( -) conformation. The nearly zero (≈10 meV) Stokes shift between absorption and emission spectra of the PFO -conformation, and the high vibronic resolution of the emission spectrum obtained with excitation at 438 nm, show that the conformations of the ground and of the lowest energy excited states are very similar.…”
Section: Optical Properties At Room Temperaturesupporting
confidence: 62%
See 1 more Smart Citation
“…17 The emission vibronic peaks identified in Figure 1 at 2.82, 2.65, and 2.48 eV match the values of 2.81, 2.65, and 2.49 eV of the -phase emission spectrum in PFO films at room temperature. 13 The similarity between the fluorescence spectrum of PFO/ MCH solutions obtained upon excitation at 438 nm and that of the nearly planar ladder-type polymer MeLPPP, where fluorescence originates from an isolated chain, is in agreement with the PFO emission resulting from PFO chain segments with a more planar ( -) conformation. The nearly zero (≈10 meV) Stokes shift between absorption and emission spectra of the PFO -conformation, and the high vibronic resolution of the emission spectrum obtained with excitation at 438 nm, show that the conformations of the ground and of the lowest energy excited states are very similar.…”
Section: Optical Properties At Room Temperaturesupporting
confidence: 62%
“…[11][12][13][14][15] In contrast, studies on characterization of the corresponding PFO ordered state in solution are still scarce. Since the first indication by Bradley et al, 2 other reports have shown a correlation between the intensity of this red-shifted peak and the poorsolvent content in solutions of good-solvent/poor-solvent mixtures (chloroform/methanol).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the excitation light drops exponentially across the 100 nm PFO layer, therefore, the PFO emission is dominated by the first 20 nm of the thicker donor layer. Thus, the exciton would have to migrate a distance much larger than exciton dissociation length (∼10 nm) 19 to explain the observed PFO↔MEH PPV energy transfer in these structures. A more appropriate description should take into account a surface-surface interaction in the bilayers with the energy transfer rate k ET ∝ R −2 , as has been observed experimentally in Refs.…”
mentioning
confidence: 99%
“…6(a) indicates the PFO β-phase peak intensity, which appears due to the cooling temperature effect. 19,20 For the bilayer (see Table I) the lifetime term τ r 1 is assigned as the recombination lifetime of the MEH PPV acceptor. The value of 277 ps for the MEH PPV at room temperature is in agreement with other results in the literature 11,21 although this lifetime can depend on the average conjugation length of the polymer.…”
mentioning
confidence: 99%
“…Estes filmes são denominados desordenados em relação as estruturas ordenadas (cristalinas e fase ). Sabe-se que filmes de PFO produzidos a partir de uma solução de PFO diluído em clorofórmio possui uma estrutura molecular totalmente amorfa denominada na literatura de vítrea (ARIU, et al 2002;ARIU, et al 2003). Esta primeira seção trata principalmente da Estamos interessados nas propriedades ópticas do PFO resultante das transições entre os estados eletrônicos não localizados (S 0 -S 1 ), portanto, para as próximas análises serão consideradas somente a região do espectro eletromagnético próximo ao visível.…”
Section: Caracterização Espectroscópica De Filmes De Pfo Amorfounclassified